Financial services and financing mechanisms for ensuring the development of identified Sasso poultry and sorghum business models in Murewha and Mbire districts in Zimbabwe - Dawes, Michael; Mushongachiware, Rodney (CGIAR, 2024)
This report advances the Agroecology Initiative (AE-I) efforts to design sustainable financial mechanisms for Sasso production and sorghum contract farming in Zimbabwe, focusing on Output 3.8 of AE-I Work Package 3. Through stakeholder engagements, focus group discussions, and key informant interviews in Mbire and Murehwa districts, the report identifies inclusive financial solutions to address the main barriers faced by smallholder farmers, such as high interest rates and lack of collateral. Key mechanisms proposed include tailored microfinance options via partnerships with institutions like Zambuko Trust, enhanced community-based financing by upgrading Internal Savings and Lending Schemes (ISALs) to Savings and Credit Cooperative Organizations (SACCOs), and digital financing models using platforms like EcoCash. Additional strategies involve contract farming agreements to ensure stable market access, credit guarantees to mitigate lending risks, and insurance options to manage climate and production risks. These financial tools create a more accessible and resilient financial ecosystem, supporting the long-term sustainability of agroecological business models in Sasso production and sorghum farming. By facilitating affordable and secure funding pathways, the report makes recommendations to empower smallholder farmers to ontinue their operations sustainably and with reduced financial risk.